Experimental study on mechanical and fracture-seepage characteristics of sandstone under hydro-mechanical coupling - Jiawei LI; Yujun ZHANG; Jie XIAO; Youwei LI; Zhiwei ZHANG (Meikuang Anquan)
In order to explore the fluid-solid coupling feedback characteristics of rock under the action of hydro-mechanical coupling, the triaxial and pore water pressure loading tests of saturated sandstone were carried out by using the rock mechanics multifunctional test system. Three groups of confining pressures of 10, 15, 20 MPa were set up, and the pore water pressures of 0, 20 %, 40 % and 60 % were set up under each group of confining pressures. Then, the influence of confining pressure and pore water pressure on the mechanical parameters of sandstone is analyzed. The damage evolution characteristics of the specimen under hydro-mechanical loading were analyzed by comparing the acoustic emission response characteristics. The permeability variation curve in the whole stress-strain process is obtained, and the fracture-seepage coupling analysis of rock mass is carried out in combination with the deformation and failure characteristics of sandstone. The test results show that: the peak strength and elastic modulus of sandstone increase with the increase of confining pressure, and are negatively correlated with pore water pressure, and Poisson’s ratio is positively correlated with pore water pressure. The greater the confining pressure, the stronger the compliance of the linear relationship. The variation of the peak strength of sandstone with confining pressure and pore water pressure follows the Mohr-Coulomb strength criterion. The acoustic emission events with higher energy levels occurred at the junction of the on-line elasticity and servo voltage stabilization stages, and the cumulative ringing count and energy curve showed a stepwise upward trend with the same frequency as the stress. The permeability evolution curve shows that “the permeability decreases rapidly at first, then decreases steadily in the middle zone, then rises rapidly, then rises sharply, and then is basically stable”. The permeability of high confining pressure specimens increases exponentially with the increase of water pressure, while the permeability of medium and low confining pressure specimens increases exponentially with the increase of water pressure. The critical stress condition of shear failure of rock self-rupture angle under hydro-mechanical coupling is given, and the rupture angle increases with the increase of water pressure.